Ethics perspective and regulation of plagiarism in Higher Education - Hengki Wijaya; Kara Elizabeth Gruber (Center for Humanities and Innovation Studies, 2018)
Plagiarism is no longer a mere issue, but it is a global fact that this disease has attacked higher education, and regarding ethics, immoral and irresponsible academics has shaken the world of education. Plagiarism has become a systematic virus that must be tackled from the root of the problem. Plagiarism is the responsibility of higher education with the government in which the Indonesian government of higher education has already established its legislation on plagiarism and colleges elaborate on it in their respective academic rules. The prevention of plagiarism begins with building a winning, honest, anti-plagiarism, and responsible mentality. It also provides a plagiarism prevention system manual (manual regulation and regulation through editorial team, plagiarism law socialization, honest and responsible culture building), as well as the use of anti-plagiarism software in college and internet and mobile browsing. Plagiarism at a high altitude can kill the creativity and wealth of thinking of pouring new ideas into work. Students who do plagiarism means to have shut down their intellectual honesty in their work. While systems that allow plagiarism to occur that they have shut down the integrity of students in work and destroy the creativity of other students in college who uphold honesty in the work.